FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PELAKU UMKM TERKAIT PELAPORAN KEUANGAN BERDASARKAN SAK ETAP - Rivaldo Maestro Putra (2017)
This study aims to determine the factors that influence SMEs related to financial reporting based SAK ETAP. Respondents who researched is pera SMEs in Jakarta and Bekasi. Data collection techniques in this study using primary data by distributing questionnaires to 90 respondents. Data processing techniques performed using SPSS 21. The variables studied are based on education level, Size of Business, Enterprises Old Stand and Perceptions Related SMEs Financial Reporting Based on SAK ETAP. partially showed significant influence education level of the perception of SMEs Related to Financial Reporting Based on SAK ETAP, the absence of significant effect Size Enterprises against the perception of SMEs Related Financial Reporting Based on SAK ETAP, and the absence of not significant influence Lama Business Standing on the perception of SMEs Related Financial reporting Under SAK ETAP. From the research simultaneously showed a significant relationship between the variables education level, Size of Business, Old Business Standing MSME Perceptions Related to Financial Reporting by SAK ETAP.